2018
DOI: 10.1002/jctb.5581
|View full text |Cite
|
Sign up to set email alerts
|

NIR‐responsive nanomaterials and their applications; upconversion nanoparticles and carbon dots: a perspective

Abstract: Near‐infrared (NIR) light responsive materials have received much attention for diverse applications due to their excellent optical properties. This type of material exhibits upconverted luminescence, a non‐linear optical process in which two or more low energy photons, usually from NIR light irradiation are transformed to high energy photons emission through energy transfer upconversion, excited state absorption, photon avalanche or multiphoton absorption. The NIR range of excitation source is favorable for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…11,12 Owing to their exceptional properties, UCNPs are promising in a wide range of applications e.g., (bio)sensing, solar cells, theranostics, and bioimaging. [13][14][15][16][17] Although NIR-LSM was not initially conceived to be used with UCNPs, this technique has been adapted perfectly to imaging them since their absorption and the NIR-LSM excitation occur in the same region (specifically, in the NIR). 18,19 Moreover, the long lifetime of UCNP emissions makes it possible to avoid the undesirable auto-fluorescence from the sample by using a simple time-gating technology.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Owing to their exceptional properties, UCNPs are promising in a wide range of applications e.g., (bio)sensing, solar cells, theranostics, and bioimaging. [13][14][15][16][17] Although NIR-LSM was not initially conceived to be used with UCNPs, this technique has been adapted perfectly to imaging them since their absorption and the NIR-LSM excitation occur in the same region (specifically, in the NIR). 18,19 Moreover, the long lifetime of UCNP emissions makes it possible to avoid the undesirable auto-fluorescence from the sample by using a simple time-gating technology.…”
Section: Introductionmentioning
confidence: 99%
“…But the efficiency of most of these are largely debatable because of the severe fluorescent decay and complex modification procedures (Chao et al, 2013). Instead, CQDs are composed of graphitic microcrystalline cores with sp 2 hybridization and abundant surface area bearing polar functional groups (Chien et al, 2018). Recent reports have demonstrated that CQDs possess varied application potential owing to the characteristics of low toxicity, high water solubility, environmental compatibility, biocompatibility, and low photobleaching (Lim et al, 2015;Shamsipur et al, 2017;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Carbon-dots, also known as carbon nanoparticles, are the latest addition to the carbon-based fluorescent nanomaterial family and have been increasingly popular due to their attractive properties such as facile synthesis, biocompatibility, good aqueous stability, and unique optical characteristics. 5 Carbon-dots favor a broad range of applications such as sensing, cellular imaging, cancer therapeutics, optoelectronics, and others. 6 The potential use of carbon-dots (CDs) for iron detection has been demonstrated in many recent works.…”
Section: Introductionmentioning
confidence: 99%